188 Right Hemicolectomy with End-To-Side Circular Stapled Ileo-Colic Anastomosis: Evaluation of Outcomes in A Series Of 55 Consecutive Patients. (12th October 2021) - Angamuthu, N; Froghi, F; Shah, S; Mirnezami, R; Knowles, J
Abstract: Background: Stapled ileo-colic anastomosis is a well-established alternative to hand-sewn anastomosis after right hemicolectomy. A side-to-side configuration (SSA) is the option commonly practiced. This study describes our experience using a less well described technique, using an end-to-side circular stapled ileo-colic anastomosis (ESSA). Method: Consecutive adult patients undergoing a right or extended- right hemicolectomy with ESSA for colonic cancer between July 2013 and March 2020 were included. Perioperative outcomes including anastomotic leak and anastomotic bleeding were extracted from a prospectively maintained institutional database. The Clavien-Dindo classification was used to stratify post-operative complications. Data are presented in medians and IQR. Results: Right hemicolectomy with circular stapled ESSA ileo-colic anastomosis was performed in 55 consecutive patients (M:F 26:29) by a single surgeon at a tertiary referral centre. Over half of patients (54.5%, 30/55) were in the 8 th and 9 th decades of age with a median BMI of 26.5 (IQR:24-30.7). Median postoperative length of stay was 6 days (IQR:4-8) and the overall morbidity rate was 34.5% (19/55). Anastomotic leak and anastomotic bleeding were seen in 5.45% (3/55) and 3.64% (2/55), respectively. None of the patients with leak or bleeding needed a re-operation. Conclusions: In comparison to the widely used SSA type of ileo-colic anastomosis, the ESSA configuration using a circular stapling device is a viable option for restoring bowel continuity after right colonic resections with comparable results. Potential advantages of this approach include avoidance of cross stapling and improved ileo-colic anatomical fidelity.